Remote, but Not Isolated—Microplastics in the Sub-surface Waters of the Canadian Arctic Archipelago - Jones-Williams, Kirstie; Galloway, Tamara S.; Peck, Victoria L.; Manno, Clara (Frontiers in Marine Science, 2021)
As the remote Canadian Arctic Archipelago (CAA) becomes increasingly connected to the rest of the world, there is an impetus to monitor the possible impact of this connectivity. The potential for increases in localised sources of plastic pollution resulting from the increasing navigability of the remote north has yet to be explored. Here we investigate microplastic samples which were collected aboard the Canadian Coast Guard Ship (CCGS) Amundsen in the summer of 2018 using the underway pump and a filtration system with Fourier transform infrared analysis. We investigate the character, abundance, and distribution of microplastic particles and fibres in the sub-surface waters across the Canadian Arctic and add to the limited dataset on plastic pollution in this region. We find that there are low concentrations of microplastics ranging from 0 to 0.282 n L–1 (average 0.031 ± 0.017 n L–1), comprising 71% polyester and acrylics. We investigate the size distribution of retained particles and fibres on three different filter mesh sizes connected to the underway pump (300, 100, and 50 μm) and find that a 300 μm mesh and a 100 μm mesh retain only 6 and 56%, respectively, of the total particles and fibres. We explore the role of shipping as a potential source of textile fibres and we suggest that future monitoring of plastics in the Canadian Arctic should use the current shipping fleet to monitor its own plastic footprint, utilising the underway pump and mesh sizes < 100 μm.